A bibliometric analysis of emotional eating in obesity research - Anindita, Yustika Izziyatu; Febriyana, Nining (Edelweiss Applied Science and Technology, 2025)
Emotional eating is a complex behavioral phenomenon that plays a significant role in obesity and is influenced by psychological, environmental, as well as biological factors. Therefore, this research aimed to conduct a bibliometric analysis to map the trends in emotional eating related to obesity, providing insights into the evolution, key contributors, and emerging themes. Data were extracted from the Scopus database, covering publications from 1983 to 2024, and analyzed using VOSviewer with the Biblioshiny R package to visualize keyword co-occurrences and thematic trends. The results showed a steady increase in scholarly attention, with contributions from psychology, nutrition, and medical sciences. The most influential countries in the domain included the United States, the United Kingdom, and European nations, with significant institutional collaborations. Meanwhile, keyword analysis reported dominant research themes such as stress-induced eating, cognitive-behavioral therapy, emotional regulation, and neural mechanisms of food consumption. Different studies were increasingly focused on intervention strategies to mitigate the impact of emotional eating on obesity, emphasizing mindfulness-based therapies and personalized nutrition methods. Despite the growing literature, gaps remained in understanding cultural variations in emotional eating and the long-term effects of interventions. In this context, future research should integrate multidisciplinary methods, including neuroscience, genetics, and social sciences, to develop effective prevention and treatment strategies. Based on the description, this research contributed to the field by providing a comprehensive mapping that informed policymakers and healthcare professionals in designing targeted interventions for obesity management. By showing key trends and research gaps, the bibliometric analysis served as a foundation for future research on emotional eating and its implications for public health.